Innovative Architectural Learning: A Case Study on Multidisciplinary and Experiential Teaching Methods - Moreira Pinto, Luis; Emin Guner , Muhammet (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2024)
This study explores an innovative approach to architectural education, integrating multidisciplinary and experiential practices to enhance student creativity, spatial perception, and problem-solving skills. Traditional studio-based teaching methods are reimagined by incorporating diverse activities such as storytelling, sketching, filmmaking, and scenario development. These methods encourage students to develop multidimensional thinking and effectively communicate complex design ideas. The research unfolds in two main phases: the transformation of a mundane urban space into a city attraction and the subsequent marketing of the design. Students engage in hands-on activities, including observational drawing, narrative construction, comic book creation, and short film production, fostering a deeper understanding of spatial dynamics and user engagement. Feedback sessions and peer evaluations ensure iterative learning and practical application. A case study involving the redesign of a "boring" street demonstrates the efficacy of this methodology, revealing increased student motivation, creativity, and interdisciplinary collaboration. However, challenges such as balancing regulatory compliance with creative exploration and the limited integration of advanced digital tools like 3D modeling and virtual reality were identified. The study underscores the necessity of adapting architectural curricula to meet contemporary professional demands, emphasizing user-centered design and advanced technological integration. This alternative pedagogical framework highlights the importance of fostering cultural exchange, peer learning, and professional preparedness. While the findings suggest a positive impact on student engagement and skill development, maintaining academic rigor within this gamified and interactive learning environment remains crucial. Ultimately, this approach not only prepares students for the complexities of modern architectural practice but also inspires innovative contributions to society.